Towards Smart Agriculture: Analysis of Agricultural Digitalization and Social Engagement in Indonesia - Corinna, Salya Elva; Hardianto, Aldi; Aji, Ganjar Ndaru; Gunawijaya, Salsabila; Hisna, Shania Alya (Westscience Press, 2025)
Agricultural digitalization is a strategic solution for increasing productivity and efficiency in the agricultural sector in the Industrial Revolution 4.0 era. Agricultural digitalization represents a fundamental transformation that is transforming food production, distribution, and consumption systems. The main advantage of digitalization lies in its ability to effectively collect, process, and analyze data ranging from weather information and soil characteristics to crop yield estimates. This study used a scoping review method to examine the literature related to the implementation of digital technology in Indonesian agriculture, focusing on the benefits, challenges, and the role of agricultural extension workers. The study results show that technologies such as IoT, AI, and GIS can drive increased agricultural yields, although their adoption is still limited to groups of farmers with high digital literacy. Age, education, infrastructure, and socio-cultural dynamics also influence technology acceptance. The Social Shaping of Technology approach emphasizes that the success of digitalization is influenced by the social context and the active participation of various parties. Challenges such as resistance to change, lack of training, and infrastructure gaps need to be addressed through inclusive cross-sector collaboration. Further research is recommended to explore technology implementation in non-Java regions and encourage active farmer involvement in innovation.